Increasing the operational and environmental performance of a diesel power installation by utilizing water-based fuel - A. A. H, Al-Maidi; AL-Mosawi, B.T.Sh.; Al-Lami, Hayder; Yu. V., Rodionov; A. E., Lomovskikh; A. V., Sever; G. V., Rybin; Majeed, Mohammed Sabeeh; Al-Nussairi, Ahmed Kateb Jumaah (Edelweiss Applied Science and Technology, 2024)
A new device for enhancing the physicochemical properties of diesel fuel to improve the combustion process and the operational and environmental performance of diesel power plants (DPP) of agricultural machinery (AM). During regular operation, DPP indicators are decreased due to various factors including the formation of carbon deposits on the surfaces of parts, causing AM to no longer meet efficiency and environmental standards. The conducted analysis of the AM operation showed that the thermal stress of the parts is increased as a result of forming carbon deposits in the combustion chamber of the DPP. To address this issue, the proposal is to utilize a technical liquid (water) that will be directed to the combustion chamber of the DPP. This process will effectively clean the surface of the carbon deposits and prevent their future formation through the microwave action of the steam-air mixture prepared in the intake manifold. For this purpose, a device has been developed to be installed on board the SHT, integrated into the standard fuel system, allowing the preparation of watered diesel fuel. As a result of complex dynamic processing, a highly dispersed emulsion is prepared from diesel fuel and water, the combustion of which in the combustion chamber of the DSU allows for the complete removal of the formed carbon deposit. The findings show that utilizing the developed device will improve the operational and environmental performance of the DSU, increase the capacity of old equipment by up to 15%, reduce specific fuel consumption by up to 18%, and the soot content in the exhaust gases by up to 14%.